Klinische Bedeutung des HDL-Cholesterins - März, Winfried; Kleber, Marcus E. (Herz, 2017)
BackroundEach year 16-17 million determinations of high-density lipoprotein cholesterol (HDL-C) are conducted and interpreted in Germany. Recently acquired data have led to a fundamental reassessment of the clinical significance of HDL-C.MethodThis review article is based on a selective literature search.ResultsLow HDL‑C levels usually indicate an increased cardiovascular risk, particularly in primary prevention but the epidemiological relationship between HDL‑C and the risk is complex. The HDL plays a role in the back transport and excretion of cholesterol; however, the biological functions of HDL are dependent on the protein and lipid composition, which is not reflected by the HDL‑C concentration. If the composition of HDL is pathologically altered it can also exert negative vascular effects.ConclusionCompared with low-density lipoprotein cholesterol (LDL-C), HDL‑C is of secondary importance for cardiovascular risk stratification and the calculation of the LDL-C:HDL‑C ratio is not useful for all patients. Low HDL‑C levels should prompt a search for additional metabolic and inflammatory pathologies. An increase in HDL‑C through lifestyle changes (e.g. smoking cessation and physical exercise) has positive effects and is recommended; however, HDL‑C is currently not a valid target for drug therapy.